RELATIONSHIP BETWEEN EARLY MOBILIZATION AND FIRST URINARY ELIMINATION ON MOTHER POSTPARTUM - Fulatul Anifah; Rizki S Emilia; Syuhrotut Taufiqoh; Nurul F Hidayati (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2017)
Background: Early mobilization presents the ability to move freely on postpartum woman less than 4 hours postpartum with the motion of sitting, standing, and then get up to bed.However, in fact generally, postpartum mothers tend to hold urine to avoid pain in wounds on birth canal. Meanwhile, the first urine can be done with early mobilization Aims: This is to analyse the relationship between early mobilization with the first elimination urine on mothers postpartum. Methods: This was a cross-sectional study that involved 48 respondents, selected through a purposive sampling method. Data collection was done using observation sheet and fisher’s exact test for statistical analyse. Result: Of the 29 puerperal women who show early mobilization less than 4 hours postpartum, there were 23 puerperal women (53.5%) with normal urinary elimination (≤ 6 hours postpartum). While from 14 postpartum mothers who did early mobilization ≥ 4 hours postpartum mothers there are 10 (23.25%) with abnormal urinary elimination (≥ 6 hours postpartum. By fisher’s exact test we found a relationship between early mobilizations with first urinary elimination on mothers postpartum (p value = 0.002) Conclusion: It can conclude the faster the first postpartum mothers mobilise, the faster the mothers can do urinary elimination. Otherwise, the longer postpartum mothers did early mobilization lasts longer than the first urinary elimination.